PERANCANGAN VIDEO PANDUAN FITNES SEBAGAI MEDIA PEMBELAJARAN - Meimaharani, Rizkysari (Universitas Muria Kudus, 2012)
ABSTRACT Designing fitness exercise tutorial level beginner as learning and promotion media for life gym was designed to provide guidelines of good movement in the fitness training sessions for beginners, especially the gym because life member will be distributed free of charge for new members sign up. For the process of editing video tutorial software and hardware needed adequate for smooth production. The results also depend on the ability of either constituent knowledge of a general nature and especially directing, editing, creativity, and the ability of hardware, software and technology / computer. Excess video guide allows members to understand the movement is good and right to avoid unwanted injury. Not only guides the movement are presented in this video project but also the member is given petuntuk diet and proper diet for target practice can be easily achieved. Excess video guide allows members to understand the movement is good and right to avoid unwanted injury. Not only guides the movement are presented in this video project but also the member is given guide of diet and proper diet for target practice can be easily achieved. The presence of video editing technology offers convenience to an agency to educate the public through video learning and served as media promotion of a service or related agency theme of the video.